Treinamento resistido melhora o controle cardiovascular e o perfil bioquímico de ratos expostos a uma dieta ocidental no período perinatal - Santana, Michael Nadson Santos (2015)
The consumption of foods high in sodium and saturated fat but low in fiber in other essential nutrients is known as Western Diet and is directly associated with metabolic and autonomic changes and the emergence of cardiovascular disease. In addition, studies have shown that eating disorders such as lack or excess food in early life promotes structural and functional adaptations in the fetus culminating in the emergence of diseases in adulthood. The resistance training (RT) has been used as a non pharmacological therapy in the treatment of various diseases, including, cardiovascular, however, the effect of RT on the cardiovascular control mechanisms have not been fully explored. The present study investigated the effects of low intensity TR autonomic modulation and the biochemical profile of rats exposed to a Western diet during the perinatal period. Wistar rats received control diet or Western during pregnancy and lactation. The rats were divided into three groups: control (C), sedentary Western Diet (WS) and Western diet + TR (WTR). After 60 days, the animals began the protocol with TR 5 times a week for 4 weeks. After the animals were surgery to evaluate pulse interval variability and blood pressure, and baroreflex sensitivity (BRS). Blood samples were collected for biochemical analysis. The RT reduced mean arterial pressure (WTR= 108.2±3.7 vs WS= 121±2.5 mmHg, p <0.05), systolic arterial pressure (WTR= 135.2±3.1 vs WS= 151.5±3.4 mmHg, p <0.05), diastolic blood pressure (WTR= 89.1±2.8 vs 99.4±2.3 WS= mmHg, p <0.05). An increase in the BRS (WTR= 1.9±0.23 vs WS= 1.1±0.14 ms/mmHg, p <0.05). Furthermore, it was observed that the RT was able to reduce vascular sympathetic modulation when compared to the WS group (WTR= 5.48±1.033 vs WS= 8.25±1.018 mmHg2, p <0.05). Biochemical parameters, found difference in blood glucose (WTR= 116.2±4.6 vs WS= 153.8±6.3 mg/dL, p <0.05), total cholesterol (TC) (WTR= 67.0±3.8 vs WS= 85.6±3.4 mg/dL, p <0.05) and high (HDL) lipoproteins (WTR= 57.2±3.5 vs WS= 41.8±2.8 mg/dL, p <0.05) and low density lipoprotein (LDL) (WTR= 14.2±2.2 vs WS= 31.0±3.2 mg/dL, p <0.05). These results suggest that low-intensity TR promotes adaptations beneficial to the cardiovascular system, mediated by adjustments in the autonomic control mechanisms and improved biochemical profile of these animals.